The Impact of Geopolitical Risks, GDP, and Inflation on Sukuk Trade Volume in Indonesia - Tama, Muhammad Pryathama; Widiyanti, Dwi Retno (Islamic Economics and finance in Focus, 2025)
Sukuk has become an important financing instrument in Indonesia's financial system, supporting infrastructure development and economic growth. Sukuk offers an alternative source of financing for the state budget deficit and provides portfolio diversification for investors with relatively low risk due to the presence of underlying assets. This study aims to analyze the impact of geopolitical risk, Gross Domestic Product (GDP), and inflation on sukuk trading volume in Indonesia from 2011 to 2024 using the Autoregressive Distributed Lag (ARDL) method. The results indicate that geopolitical risk has a negative impact on sukuk trading volume, reflecting that geopolitical uncertainty can reduce investor interest in sukuk. GDP has a positive impact, indicating that stable economic growth encourages sukuk issuance. Inflation has a negative impact on sukuk trading volume, although its effect is not always significant, reflecting that high inflation can reduce investor purchasing power and diminish the appeal of sukuk. This study provides important insights for the government to maintain political stability and promote economic growth to keep the sukuk market attractive to investors. Meanwhile, issuers need to consider the timing of issuance and market conditions to optimize their financing strategies through sukuk.